KONSUMSI DAN INVESTASI SERTA PERTUMBUHAN EKONOMI SUMATERA BARAT - Shandra, Yosi; Amar, Syamsul; Aimon, Hasdi (Program Studi Magister Ilmu Ekonomi, 2012)
ABSTRACT The analysis of aggregate consumption growth, investment and economic growth have been carried out in West Sumatra. The purpose of this study was to clarify the effect of consumption, investment, taxation, government spending, consumption of the previous period, the interest rate and disposal revenue to GDP in West Sumatra. The study was conducted with descriptive and associative with the use of secondary data in the form of time series, 1994 -2010. The results on the First Hypothesis suggests that the development of consumption, the development of investment and the development of government spending together influential significantly to economic growth. Partially, the development of consumption and the growth of government spending significantly and positively to affect economic growth, then the development of a positive and significant effect of investment on economic growth. In the Second Hypothesis together previous period consumption growth and development of disposibel income and significant positive impact on the development of consumption. Partially, the previous period consumption growth and positive impact on the development of consumption was not significant and influential positive revenue development disposibel and significant to the development of consumption. Then on the Third Hypothesis jointly the credit interest rate of investment and economic growth has no effect on the development of significant investment. Partially, credit interest rates negatively and significant investment toward the development of investment and economic growth has positive influence on the development and significant investment. The Fourth Hypothesis proved to be influential economic growth on the development of the tax was not significant in West Sumatra. Government efforts need to be able to continue to increase government spending or reduce taxes by increasing the production of regional output. In addition to government efforts are needed to further improve the quality of human resources by providing education and training, scholarships and employment opportunities in labor- intensive system. To overcome the problem of development of investment the government needs to take expansionary monetary action is by controlling interest rates in order to increase investment development. Key words : consumption, investation, government spending, economic growth